Low Income and Stroke Rehabilitation: A Tale of Two Clients - Sarah Bernard; Katrine Sauvé-Schenk; Mary Egan (Scholarworks @ WMU, 2019)
The objective of this paper is to provide a theoretical and practical understanding of these challenges with re-engagement in personally valued occupations following stroke, as well as to make recommendations to guide practice. First, we review the current understanding of the impact of low income on the experience of rehabilitation and on later participation in the community. Second, we present two theoretical approaches to understanding the impact of income: social determinants of health and intersectionality. We then present the stories of two low-income stroke survivors who were treated on an inpatient stroke rehabilitation unit. These stories serve to illustrate how the experiences of rehabilitation can differ based on social location and how an intersectionality approach can improve a rehabilitation team's appreciation of the potential impact of a person's unique context. Finally, we discuss the clinical implications and make recommendations for future research.